The Economic Impacts of Renewal Energy on Local Economies: The Case of Solar Energy in Japan - Hayami, Hitoshi; Nakamura, Masao (Journal of Technology Innovations in Renewable Energy, 2017)
Various alternative renewable energy sources have been proposed and implemented. These energy sources, which generally do not rely on fossil fuel, are distinguished from the traditional large scale energy projects in a number of ways. On the other hand, the circumstances surrounding renewable energy sources currently under use are characterized by their small size and scale and their economic impacts are generally local. For example, wind mills based electric power generation uses locally available wind currents and geothermal power generation uses locally available geothermal heat sources. Similarly, solar power generation uses solar power available in the local regions. These imply that the economic impacts of most renewable energy sources currently in use are local. We estimate our model using cross-sectional data of regional economies measured at the prefecture level in Japan. This will allow us to estimate the impacts of certain government policy variables at the regional level as well. One hypothesis we consider in this paper is that while solar power is still negligible in terms of its impact on Japan’s national economy, it has some economic impacts on the economies of the regions where they are located.